Goalkeeper's strategies for penalty kicks - Souza, César Filippini de (2023)
Football is a worldwide cultural phenomenon due to the massification process that includes not only the practicing public, but also the people who only consume the sport. Match analysis has been a tool widely used to evaluate the performance of teams and thus explore the positive and negative points, in addition to the factors that can influence the result of the match. The penalty is an especially important moment for football, as it has high goal rates and a high occurrence between games. Thus, this study analyzed penalty kicks from the UEFA Champions League (2016-2020) to analyze the strategies used by the goalkeeper in penalty kicks and their influence on the success of penalties. The analyzed data show that most goalkeepers use only one strategy in penalty kicks, with anticipation being the most used. Despite this, lateralization, which would be the positioning of the goalkeeper outside the center of the goal, was the strategy that proved to be more effective for the goalkeeper. In addition, goalkeepers have better rates when they use more strategies